Testing bats in rehabilitation for SARS‐CoV‐2 before release into the wild. Issue 7 (5th May 2022) - Jones, Scott; Bell, Thomas; Coleman, Christopher M.; Harris, Danielle; Woodward, Guy; Worledge, Lisa; Roberts, Helen; McElhinney, Lorraine; Aegerter, James; Ransome, Emma; Savolainen, Vincent
Abstract: Several studies have suggested SARS‐CoV‐2 originated from a viral ancestor in bats, but whether transmission occurred directly or via an intermediary host to humans remains unknown. Concerns of spillover of SARS‐CoV‐2 into wild bat populations are hindering bat rehabilitation and conservation efforts in the United Kingdom and elsewhere. Current protocols state that animals cared for by individuals who have tested positive for SARS‐CoV‐2 cannot be released into the wild and must be isolated to reduce the risk of transmission to wild populations. Here, we propose a reverse transcription‐quantitative polymerase chain reaction (RT‐qPCR)‐based protocol for detection of SARS‐CoV‐2 in bats, using fecal sampling. Bats from the United Kingdom were tested following suspected exposure to SARS‐CoV‐2 and tested negative for the virus. With current UK and international legislation, the identification of SARS‐CoV‐2 infection in wild animals is becoming increasingly important, and protocols such as the one developed here will help improve understanding and mitigation of SARS‐CoV‐2 in the future.